Understanding Islamic capital market - Norfadelizan Abdul Rahman; Zairulnizad Shahrim; Razli Ramli (IBFIM, 2014)
This book is designed to focus on the area of Islamic Capital Market (ICM) with the aim to equip the readers with solid knowledge in Islamic capital market industry as well as to develop necessary skiil and expertise to deal with issues and problems prevailing in the ICM practices. With the rapid expansion and innovation in ICM industry, it is hoped that this book will be a source of reference and learning.